Remediation of Cadmium-contaminated Soil by Cadmium-resistant Sulfate-reducing Bacteria - He WANG; Minglin WU; Yongli QIN; Wanying ZHENG; Yongrong JIANG; Xuejun LI (Kuangchan zonghe liyong, 2025)
In order to investigate the cadmium reduction effect of cadmium-tolerant sulfate-reducing bacteria (SRB) on cadmium-contaminated soil, cadmium-tolerant SRB was screened and isolated using cadmium-tolerant sulfate-reducing sludge as seed sludge, and was injected into soils with different degrees of cadmium contamination (mild, moderate, and severe) to investigate the fugitive morphology of soil cadmium, the changes in sulfate reduction activity and microbial community structure. The results showed that after 53 d of Cd-tolerant SRB remediation, the total Cd content of soils with different Cd contamination levels did not change significantly, the proportion of unstable Cd (exchangeable state, carbonate-bound state) decreased from the initial 45%～68% to 26%～40%, and the proportion of stable Cd (Fe-Mn oxidation state, organic-bound state, residue state) increased significantly from the initial 30%～50% to 60%～75%. The effective passivation of cadmium in soils with different degrees of heavy metal cadmium pollution was achieved. The sulfate content of soils with different degrees of cadmium pollution showed a trend of gradually decreasing and then increasing during the remediation process, while the sulfate reduction activity gradually decreased, and there was regeneration of sulfate in the system. The change trend of each contaminated soil bacterial phylum during the remediation of cadmium-tolerant SRB was more or less the same, with Proteobacteria and Bacteroidetes as the main phylum, Desulfosporosinus and Desulfobacca as the main SRB genera, and their abundance gradually decreased during the remediation process, while sulfur-oxidizing bacteria had a tendency to increase. This shows that cadmium-tolerant SRB can reduce the content of unstable cadmium in cadmium-contaminated soil, and reduce the mobility of cadmium, but it is necessary to optimize the remediation parameters to enhance sulfate reduction and inhibit sulfur oxidation in the remediation process.